The Impact of Training and Professional Development on Enhancing Efficiency, Growth, and Sustainability of Family Businesses in the Kingdom of Saudi Arabia - Natheer, Hanan Abdullah (Journal of Economic, Administrative and Legal Sciences, 2025)
Family businesses have a large and effective role in the economy in general, whether among developed or developing countries, because they represent the largest portion of small and medium enterprises. In light of this general development, the importance of training and professional development has begun to emerge as one of the basic elements for achieving sustainability for these companies and enhancing their efficiency. In the Kingdom, this is because training is a strategic tool that contributes to improving the organizational performance of the company as a whole. Therefore, this research sought to work on the impact of training and professional development on enhancing efficiency, developing and sustaining family businesses in the Kingdom of Saudi Arabia, by asking a question and working to reach to answer him, this question is: What is the impact of training and professional development programs on the efficiency of employees in family businesses in the Kingdom of Saudi Arabia? The research used the descriptive analytical method to answer these questions. The research reached results including: There are no statistically significant differences at the 0.05 level of significance in all average dimensions of the questionnaire on the impact of training and professional development on enhancing efficiency and developing and sustaining family businesses in the Kingdom of Saudi Arabia, meaning that Years of experience do not affect opinions about the impact of training and professional development on enhancing efficiency, developing and sustaining family businesses in the Kingdom of Saudi Arabia. While there is a strong, statistically significant, direct correlation between training and professional development and the sustainability of family businesses at a significance level of 0.01, it is evident that there is a statistically significant direct impact of training and professional development on the sustainability of family businesses at a significance level of 0.01.